Normalization of biventricular strain post steroid treatment of effusive constrictive pericarditis. Issue 5 (May 2017) - Walsh, Jason Leo; Lamaa, Nader; Alam, Samir; Didi, Ahmad; Isma'eel, Hussain
Abstract: Peak left ventricular strain measured by speckle tracking echocardiography has previously been shown to normalize following pericardectomy in constrictive pericarditis, as indicated by an increase of the strain ratio between the lateral wall and septum. Here we present a case of effusive constrictive pericarditis treated with corticosteroids. Pre-treatment we observed reduced contractility of the lateral walls of both ventricles as measured by peak strain, with sparing of overall septal function, but with hypercontractility of the basal septal segment. Septal and lateral wall function normalized with corticosteroid treatment. Our observations from this case prompts investigation into the value of lateral/septal wall strain ratios in both ventricles for quantitatively monitoring the response of constrictive pericarditis to medical therapy. <Learning objective: Change in peak strain ratios between the lateral and septal walls of both ventricles may be a novel marker of response to medical therapy in effusive constrictive pericarditis.>